The joint effect of maternal smoking during pregnancy and maternal pre-pregnancy overweight on infants' term birth weight - Thanin Chattrapiban; Henriette A. Smit; Alet H. Wijga; Bert Brunekreef; Judith M. Vonk; Ulrike Gehring; Lenie van Rossem (BMC, 2020)
Abstract Background It is well known that maternal smoking during pregnancy and maternal pre-pregnancy overweight have opposite effects on the infants' birth weight. We report on the association of the combination between both risk factors and the infants' birth weight. Methods We studied 3241 infants born at term in the PIAMA birth cohort. Maternal smoking during pregnancy and pre-pregnancy height and weight were self-reported. Multivariable regression analysis was performed to assess the associations between infants of mothers who only smoked during pregnancy, who only had pre-pregnancy overweight and who had both risk factors simultaneously, on term birth weight and the risk of being SGA or LGA. Results Of 3241 infants, 421 infants (13%) were born to smoking, non-overweight mothers, 514 (15.8%) to non-smoking, overweight mothers, 129 (4%) to smoking and overweight mothers and 2177 (67%) to non-smoking, non-overweight mothers (reference group). Infants of mothers who smoked and also had pre-pregnancy overweight had similar term birth weight (− 26.6 g, 95%CI: − 113.0, 59.8), SGA risk (OR = 1.06, 95%CI: 0.56, 2.04), and LGA risk (OR = 1.09, 95%CI: 0.61, 1.96) as the reference group. Conclusions Our findings suggested that the effects of maternal smoking during pregnancy and maternal pre-pregnancy overweight on infants' birth weight cancel each other out. Therefore, birth weight may not be a good indicator of an infant's health status in perinatal practice because it may mask potential health risks due to these maternal risk factors when both present together.